Bayesian predictive model to assess BRCA2 mutational status according to clinical history: Early onset, metastatic phenotype or family history of breast/ovary cancer. Issue 6 (18th February 2021) - Leon, Priscilla; Cancel‐Tassin, Geraldine; Bourdon, Violaine; Buecher, Bruno; Oudard, Stephane; Brureau, Laurent; Jouffe, Lionel; Blanchet, Pascal; Stoppa‐Lyonnet, Dominique; Coulet, Florence; Sobol, Hagay; Cussenot, Olivier
Abstract: Background: Mutations of the BRCA2 gene are the most frequent alterations found in germline DNA from men with prostate cancer (PrCa), but clinical parameters that could better orientate for BRCA2 mutation screening need to be established. Methods: Germline DNA from 325 PrCa patients (median age at diagnosis: 57 years old) was screened for BRCA2 mutation. The mutation frequency was compared between three subgroups: patients with an age at diagnosis at 55 years old and under (Group I); a personal or family history of breast, uterine or ovarian cancer (Group II); or a metastatic disease (Group III). Frequency of BRCA2 mutations was established for each combination of phenotypes, and compared between patients meeting or not the criteria for each subgroup using Fisher's exact test. Mutual information, direct effect, elasticity and contribution to the mutational status of each phenotype, taking into account overlap between subgroups, were also estimated using Bayesian algorithms. Results: The proportion of BRCA2 mutation was 5.9% in Group I, 10.9% in Group II and 6.9% in Group III. The frequency of BRCA2 mutation was significantly higher among patients of Group II ( p  = .006), and reached 15.6% among patients of this group who presented a metastatic disease. Mutual information, direct effect, elasticity and contribution to the mutational status were the highest for phenotype II. Fifteen (71.4%) of the 21 BRCA2 mutation carriers had an aggressive form of the disease. Four (19%) of them died from PrCa after a median follow‐up duration of 64.5 months. Conclusions: Our results showed that a higher frequency of BRCA2 mutation carriers is observed, not only among PrCa patients with young onset or a metastatic disease, but also with a personal or a familial history of breast cancer.